ANALISIS KETERAMPILAN MEMBACA PERMULAAN PADA SISWA KELAS II - Simangunsong, Anisa; Siregar, Arifin (Jurnal Merah Putih Sekolah Dasar, 2024)
This study aims to analyze the initial reading skills of class II students at SD N 173179 Sipahutar District North  Tapanuli Regency T. A 2023/2024 as well as the factors inhibiting low initial reading skills. This research is a descriptive qulitative research. The number of participants in this research was 20 people, namely 19 studentd of class II at SD N173179 who were given an oral test to analyze their initial reading skills and 1 class teacher. Data collection uses oral test techniques, interviews anda documentation. Based on the data that has been obtained, there are 19 students in class II SD N 173179, 8 students have fairly good reading skills and 11 students have low initial reading skills and have initial reading difficulties. Factors inhibiting the low initial reading skill of second grade SD N 173179 consists of two factors. The internal factorsis the lack of interest of students in learning to read. Intially, students thin that reading is a boring activity and dificult to do. The external factor is the lack of attention and guidance from parents regarding children™s leraning to read activities at home. As well as the lack of optimizing the use of the libraries in schools  and the lack of completeness of book for beggining learning reading.Keywords: beginning reading, elementary school students, inhibiting factors